Pengembangan Media Pembelajaran Busy Book Materi Cuaca Tema 5 untuk Kelas III - Karlina; Nurlaeli; Tastin; Aquami; Ayu Nurshawmi (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2022)
This study aims to determine: (1) Produce media products Busy Book 3- dimensional learning, (2) Produce Busy Book learning media valid, (3) Produce Busy Book learning media for students class III at SD Negeri 1 Berkat to the practical. The method used is R&D research and development methods using the model ADDIE development, namely, Analysis, Design, Development, Implementation and Evaluation, data collection used in the form of tests, questionnaires, and documentation. Test the validity and practicality of the data using an assessment of the Questionnaire. The subjects of this study were third-grade students at SD Negeri 1 Berkat As many as 20 students, therefore conclusions can be drawn in the form of (1) Produce Busy Book learning media for third-grade students at SD Negeri 1 Berkat the valid blessing is seen from the results of the media expert’s validity questionnaire, which is obtained a score of 95.38, linguistic expert validation obtained a score of 93.33 and expert validation material with a score of 96.66, (2) produce learning media Busy Book for third graders at SD Negeri 1 Berkat which is practical with grades an average of 85.95.